Analisis Strategi Pengelolaan Wakaf sebagai Bisnis Sosial Islam - Study Kasus Yayasan Wakaf Produktif Pengelola Aset Islami Indonesia - Siti Karimatul Akhlaq; Bayu Taufiq Possumah; Eng Saiful Anwar (ILTIZAM Journal of Shariah Economics Research, 2021)
This research aims to analyze (i) how the productive waqf management strategy carried out by the Yayasan Wakaf Produktif Pengelola Aset Islami Indonesia and (ii) Priority of the benefits, opportunities, costs and risks (BOCR) of the Yayasan's development strategy in managing its productive waqf projects. The respondents in this research consisted of experts, academics and waqf practitioners. The type of this research is qualitative and the data analysis method used in this research is the two-story of Analytic Network Process (ANP) with super-decision software. In this research, the aspects of benefits, opportunities, costs and risks (BOCR) are divided into 2 aspects, first internal aspects; aspects which have point of view from the perspective inside the institution and the second external aspects, aspects seen from the point of view outside the Yayasan. Before the existing strategy of the Yayasan is analysed using the ANP- BOCR method, the researcher maps out the strategy into the business model canvas (BMC). The results of the research, the strategies that have been carried out by Yayasan are (1) Intensive good use of Nazir who is competent and knows knowledge about waqf, and (2) the feasibility study before choosing a business for waqf funds and (3). Productive Collection of waqf funds using a personal approach to potential waqifs. This study shows that the three strategies above which are carried out by the Yayasan - are things that most respondents preferred, showed a rater agreement (W) at the the level of agreement between respondents at the medium level, namely = 0.39 - which is in accordance with the study result of long-term strategy. The Yayasan has proven to generate maximized and sustainable profits which have been distributed to mawquf alayh in accordance with the initial objectives of its project.